Wind farm noise negatively impacts the calling behavior of three frogs in Caatinga dry forests - Rogério Ferreira de Oliveira; André Felipe de Araujo Lira; Valentina Zaffaroni-Caorsi; Matheus Leonydas Borba Feitosa; Geraldo Jorge Barbosa de Moura (PLoS ONE, 2025)
Acoustic signals play a fundamental role in the lives of anurans. With the increasing prevalence of wind farms in Caatinga ecosystems, our goal was to assess whether the noise generated by this energy source poses a threat to anuran communication. We analyzed acoustic parameters of the advertisement calls from 181 adult males, of the species Scinax pachycrus, Scinax x-signatus, and Physalaemus cicada. Call activity was recorded across noise gradients in 19 temporary ponds with similar vegetation structures, distributed in two wind farms. Our results revealed a significant relationship between wind turbine noise and changes in acoustic parameters of the three species, distinctly influencing their spectral and temporal parameters of the advertisement calls. Dominant frequency, frequency range of Scinax pachycrus were affected by the noise, decreasing in noisier temporary ponds, while Scinax x-signatus decreased call amplitude and call pulses. On the other hand, Physalaemus cicada showed changes only in temporal variables, with reductions in call duration and call pulses, and an increase in call rate to cope whit noise in temporary ponds. Therefore, noise pollution becomes particularly concerning for the anurans of the Caatinga, as the areas of greatest interest for wind power generation overlap with priority areas for biodiversity conservation.